An Assessment Tool for Energy Audit of Buildings in Jordan Using Simulation - Al-Jbour, Abeer; Abutayeh, Heba; Qawasmeh, Bashar R. (Global Journal of Energy Technology Research Updates, 2024)
In developed nations, there's a growing concern for sustainable energy management, particularly regarding enhancing energy efficiency in both existing and new buildings. The methodology presented considers the energy modelling and simulation of manufacturing buildings through thermal and electrical loads calculations using Dymola/Modelica software. The thermal model is built with the primary components of Dymola along with available models to calculate the heating and cooling loads, whereas the electrical model was calculated using consumption patterns, then the total model was validated against real measurements where the error percentage was 9.96 %. The yearly heating load baseline was 6295 kWh/y and for cooling 46276 kWh/y., the exciting potential for energy- savings and load flexibility, and some suggestions for improving consumption were pointed out and identified. It found that the highest influence on the thermal load reduction was using the double glaze with shading with 61% of the energy-saving options, then replacing the fluorescent with LED with 30%, and finally, the roof insulation was the least influence with 9.5%. For the total consumption, the highest percentage was for replacing the fluorescent with LED with 78% of energy-saving options, then double glaze with shading, and finally the lowest is for the roof insulation.